Chord end distance effect on RHS connections. (May 2020) - Bu, Xiao-Ding; Packer, Jeffrey A.
Abstract: The strength of a welded hollow structural section (HSS) connection is compromised when the connection is located near the end of an open chord member. Recently, some contemporary codes and standards, such as prEN 1993-1-8 and AISC 360, have proposed a minimum end distance so that the connection strength is not affected by this end effect. Experimental tests have now been performed to study the end effect for rectangular hollow section (RHS) connections. A numerical study with a broader range of parameters has been completed, in which non-linear finite element (FE) models are validated against 14 laboratory experiments and are used to generate 264 numerical models, with multiple geometric connection parameters varied. From this numerical and experimental database, a required minimum chord end distance is proposed, in order that a connection may achieve full strength. This is given as a lower bound for both branch compression and tension loading conditions, for all potential limit states. If the connection end distance is smaller than this requirement, the end effect is proposed as a strength reduction factor. Highlights: Non-linearfinite-element modelling performed for asymmetric RHS connections. Effect of distance, from an RHS branch to an RHS chord open end, examined. Influence of geometric parameters (e.g. β, 2γ) with end distance is shown. Minimum required end distance obtained, to avoid a reduced connection strength. Reduced connection capacity determined, for very low end distances.